Natural gas consumption and economic growth nexus for top 10 natural Gas–Consuming countries: A granger causality analysis in the frequency domain. (15th December 2018) - Aydin, Mucahit
Abstract: In this study, the relationship between natural gas energy consumption and economic growth has been examined within the framework of the growth model for the top 10 natural gas–consuming countries from 1994 to 2015 using the recently developed panel Granger causality tests that allow for country-level heterogeneity. The results show that there is a long-run relationship between natural gas consumption and economic growth, and natural gas consumption has a significant and positive impact on economic growth in the long run. The Granger causality analysis in the frequency domain test results could be summarized as following. First, in terms of causality running from economic growth to natural gas consumption, there is a temporary relationship for Germany, and a permanent relationship for the United Kingdom and Thailand. Second, in terms of causality running from natural gas consumption to economic growth, there is a temporary relationship for Thailand. The main finding is that countries should increase the use of natural gas consumption to ensure energy security, reduce energy dependence, reduce carbon dioxide emissions, and encourage economic growth. Highlights: The relationship between natural gas consumption and economic growth is examined. Top 10 Natural Gas–Consuming Countries are covered. Frequency domain causality analysis is used. Country-based results are obtained and made inferences. Overall, increase the usage of natural gas energy to promoting economic growth.